Advanced back grinding of semiconductor wafers using an angle-feedback TTV compensation controller - Hwang, Byung-Hyun; Park, Kyoung-Su (Precision engineering, 2025)
As the semiconductor industry advances toward higher performance and integration, precise wafer back grinding has become increasingly vital. This study introduces an innovative, in-house wafer back grinding system that features a non-contact laser displacement sensor for inline Total Thickness Variation (TTV) measurement—eliminating the need to detach wafers during processing. By integrating real-time measurement and feedback, the proposed system minimizes process-induced errors, streamlines workflow, and significantly boosts manufacturing efficiency. A novel algorithm based on rotation matrix-based angle compensation adjusts the α and β tilting angles to align the wafer and grinding wheel planes accurately. Experimental validation shows that TTV was improved by an average of 510 % with TTV distribution errors reduced by 74.6 %, bringing values consistently within micron-level tolerances. This research marks a major step toward real-time optimization of the back grinding process. The proposed method is compatible with both rough and fine grinding wheels, offering scalable improvements in wafer quality and throughput. These results underscore the critical role of integrated measurement and adaptive angle-feedback algorithms in next-generation semiconductor manufacturing. •l Innovative back grinding system with in-situ TTV measurement and rapid feedback without wafer removal.•l Angle-feedback algorithm boosts TTV performance via real-time angular error compensation.•Technology greatly increases UPH with instant TTV error detection and correction.